A Case of CIED-Associated Endocarditis and Septic Emboli Requiring Lead Extraction, AngioVac Suction, and Pulmonary Endarterectomy - Green, Erik A (Cureus, 2020)
Cardiac Implantable Electronic Devices (CIED)-associated infective endocarditis complicated by septic emboli and acute on chronic pulmonary hypertension is rare. We present a case where pulmonary thromboendarterectomy was required for treatment. A 55 year-old man with a history of myocardial infarction and ischemic cardiomyopathy status-post ICD placement 8 years prior presented with bacteremia, infected ICD, and tricuspid valve vegetation. He underwent CIED extraction along with the use of the AngioVac suction device to remove right ventricular and atrial vegetations. However the patient had persistent valvular vegetation and bilateral sub-massive pulmonary emboli. Pulmonary angiography showed filling defects in the lobar and segmental arteries. Percutaneous attempts at embolectomy were unsuccessful and he therefore underwent a pulmonary endarterectomy surgery (PTE). This case of CIED- associated endocarditis demonstrates the importance of early aggressive treatment of such infections. Guidelines recommend compete CIED system removal when there is associated infection. The AngioVac is a novel system for removal of right-sided vegetations and thrombi; however, complications such as distal embolization can occur. PTE surgery for septic emboli is rare. However, cases of such treatment as is presented here can be successful and may be necessary should percutaneous methods fail.